Language Attitudes Down Under: Attractiveness and Perceived Similarity of English Accents - Hooft, Ellen 't (Student Undergraduate Research E-journal!, 2017)
Perceived similarity is an uncommon construct in previous studies on attitudes towards accents. This study focuses on how Australian adolescents rate the attractiveness of four English accents and how similar the participants judge these accents to be to their own accent. This study uses a verbal-guise technique and a survey to question 66 Australian adolescents. The speakers used in this study represent a General American, a standard British (RP), an Australian, and a New Zealand accent. The Australians rate the Australian accent highest in attractiveness and similarity. This study found that attractiveness and similarity in this context are positively correlated.